Hidden Diversity of African Yellow House Bats (Vespertilionidae, Scotophilus): Insights From Multilocus Phylogenetics and Lineage Delimitation - Demos, Terrence C.; Webala, Paul W.; Bartonjo, Michael; Patterson, Bruce D. (Frontiers in Ecology and Evolution, 2018)
The genus Scotophilus contains 21 currently recognized species ranging throughout Africa and Southeast Asia. Among the 13 species recognized from continental Africa, systematic relationships remain poorly understood. Taxonomic uncertainty regarding names, suggestions of polytypic species complexes, and undescribed cryptic diversity all contribute to the current confusion. To gain insights into the systematics of this group, we inferred single locus and multi-locus phylogenies and conducted lineage delimitation analyses using seven unlinked genes for specimens from across Africa. Recent collections from Kenya allowed us to carry out population-level analyses for the diverse assemblage of East African Scotophilus. Multi-locus coalescent delimitation methods indicated strong support for three recently named lineages thought to be restricted to Kenya and Tanzania; it also uncovered two new distinctive lineages at present known only from Kenya. Subsequent taxonomic assessments that integrate these genetic data with phenotypic, distributional, and/or ecological traits are needed to establish these lineages as valid species. Nevertheless, as many as 15 Scotophilus species may occur in continental Africa, 10 of these in Kenya alone. Our analysis highlights the importance of population-level surveys for the detection of cryptic diversity in understudied regions such as the Afrotropics.